Apparent viscosity of high-density fluidized bed and synergistic effect of density and apparent viscosity on particle separation. Issue 2 (1st June 2023) - Bai, Yuqi; Zhao, Pengfei; Guo, Mengyao; Yan, Guanghui; Zhou, Chenyang; Sun, Zongsheng; Gao, Tianyang; Zhang, Bo
ABSTRACT: For gas-solid fluidization separation, mineral particles are separated under the joint action of bed density and apparent viscosity. In present study, the apparent viscosity of high-density binary mixture media was investigated by the falling ball method. Moreover, the significant effects of bed density and apparent viscosity on simulated mineral pellets and their interactions were investigated. The apparent viscosity model of high-density gas-solid fluidized beds was modified, and it was found that the Pearson correlation coefficient is 0.86. The results show that the apparent viscosity of high-density gas-solid fluidized bed decreases with increasing fluidization gas velocity. When the fluidization number is higher than 1.3, the apparent viscosity is basically stable in the range of 3.96–5.21 Pa·s. Under low apparent viscosity, when the pellet diameter is 20 mm and the density difference ∆ρ is greater than 0.27 g/cm 3, gravity is the dominant factor affecting the settling behavior of the pellet. Under high apparent viscosity, the effect of viscous resistance on the settling behavior of pellets is dominant when the ∆ρ is less than 0.27 g/cm 3 . Based on the performed analyses, the low-viscosity medium can be selected for the separation of large mineral particles. Furthermore, for high-viscosity medium, the influence of bubbles on particle sedimentation can be effectively alleviated and it can be selected for the separation of small particles. GRAPHICAL ABSTRACT: uf0001